Pracownie bursztynnicze w południowo-wschodnim rejonie gdańskiego grodu na przełomie X-XI wieku - Lepówna, Barbara (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The excavations of Gdańsk have revealed large quantities of amber artifacts. The presence of both raw material and unfinished artifacts indicates that amber was worked on the spot. Unworked amber and unfinished artifacts were mainly concentrated in excavation trenches XI, XIV and XXII located within the assumed seat of the feudal lord (fig. 1), in layers dating from the end of the 10th to the first quarter of the 11th century. Remains of at least a few workshops producing finger-rings have come to light. However, no traces of any buildings have survived. Of the 43 amber objects found in trench XI as many as 35 are unfinished finger-rings. An area of only 8 m2 in trench XIV (storage pit and layer) yielded 4,069 amber lumps and 60 unfinished finger-rings in various stages of working. Workshops concentrated in the more important quarter of Gdańsk used raw materials which were the monopoly of the prince, i.e. amber and silver (a crucible with traces of melted silver has come to light). It seems very likely that the artisans in question were working directly for the court of the prince.